Psychiatry, spirituality, and quantum science - Hitesh Chandrakant Sheth (Wolters Kluwer Medknow Publications, 2019)
It would be impossible to comprehend the complexity of a human brain by a single cell organism; similarly, it would be impossible to understand the complexity of "Reality "or "Ultimate Truth "by a human brain hampered by limitations. At best, it can arrive at approximations of truth, which would vary from a person to person and a being to being. That is why, Jain philosophy while explaining Truth stresses on "Anekāntavāda" multiple aspects of Truth or Reality. Vedas too, while explaining Truth says, "Ekam sat vipraa bahudhaa vadanti" which is literally translated as "Truth is one, but the learned ones refer to it in different names. "If a human mind is made to understand that what it claims as sole truth may be an aspect of truth or a truth distorted by its understanding, then it would be humble enough to respect and accept the opinions of other minds. This Socratic paradox (The only thing I know is that I know nothing.) may keep our mind open and flexible enough to discover the deeper truth of psychiatry, spirituality, and quantum science and may lead to their synthesis into some deeper science or truth.